Proposta para a prática do professor do ensino fundamental I de noções básicas de geometria com o uso de tecnologias - Bagé, Idalise Bernardo (2008)
This paper is part of the Informational Technologies and Mathematical Education survey line and aims at verifying the possible contributions that a Teachers Development Course , so called Curso de Formação Continuada , bring to the professional practice of teaching Geometry in the initial series of our elementary school, that is, Ensino Fundamental I . In that intent the survey question formulated was: to what extent can a workshop, with the use of technological resources, contribute to the practices of the professionals teaching the basic Geometry concepts in the initial series of our Ensino Fundamental I ? In order to answer that question, we firstly elaborated a workshop proposition with ten activities using the Building Perspective and Cabri-Géomètre softwares and applied it to a group of 30 (thirty) teachers who worked on the fourth year of Ensino Fundamental I . Such proposition is based on the theoretical presuppositions of the geometrical thought development in Van Hiele s pattern, for the elaboration of the activities, and the teachers development with the use of technology. At a second moment, the referred teachers applied the activities to their students. Design Experiments was adopted as the survey methodology, aiming at the refinement of the workshop proposition for future groups of teachers participating in it. As data collectors this survey relied on: an initial questionnaire for checking the teachers traits, the protocol of the activities developed by the teachers, a semi-structured interview to collect information about the application of the workshop with the students and a final questionnaire intended to evaluate the workshop. Analyzed all the data, the conclusion was that the proposition allowed the teachers to notice the importance of the teaching of Geometry at the initial series of Ensino Fundamental I and the possibilities the software Cabri- Géomètre offer in enriching the development of the geometric concepts. At the end, based on the analyses done throughout this job, as well as on the suggestions from the participant teachers, there s the proposition of a new, enhanced workshop